Dampak Pengembangan Pariwisata Di Pantai Cemara Cipanglay Terhadap Pemberdayaan Masyarakat - Asri Fitria Dwiyanti; Dindin Solahudin; Agus Ahmad Safei (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
Initially, Cemara Cipanglay Beach was not productive. If it was developed in a tourist area, it would certainly affect the municipality's economic growth. This study aims to determine the strategy, process and impact of tourism development on Cemara Cipanglay Beach on community empowerment. The method used in this research is descriptive research method with a qualitative approach. The results of the study show that this tourism development strategy maximizes the strength aspect of the potential of natural resources owned, namely there are three elements of natural charm, namely the agricultural, forestry and marine sectors contained in one beach tourist object. In carrying out the tourism development process at Cemara Cipanglay Beach, it involves the role as well as the Village Government, Community Empowerment Institutions (LPM), Youth Organizations, District Leadership Conferences (Muspika), Community Mobilization Groups (Kompepar), Forest Farmers Groups (KTH), Tourism Awareness Groups and the Cidamar Village community starting from the process of planning, implementing, managing up to evaluation, the result of tourism development at Cemara Cipanglay Beach is an increase in community participation in the implementation of tourism development based on public awareness to make changes